Pengembangan Instrument Test Akurasi Tendangan Long Pass Pada Cabang Olahraga Sepakbola - Rustiawan, Hendra; Sutisna, Nana; Risma, Risma; Rohendi, Andang (Universitas Galuh, 2024)
This research aims to produce a long pass test instrument product, namely using a 3x3 meter box in which 1x1 meter has varying values while comparing it with old test instruments. The research method used is R & D (Research and Development). The results obtained have a correlation value (r) of 0.4. based on the strength of the relationship it can be said to be